Consumer credit regulation and lender market power - Zachary Bethune; Joaquin Saldain; Eric R. Young (Bank of Canada, 2024)
We investigate the welfare consequences of consumer credit regulation in a dynamic, heterogeneous-agent model with endogenous lender market power. We incorporate a decentralized credit market with search and incomplete information frictions into an off-the-shelf Eaton-Gersovitz model of consumer credit and default. Lenders post credit offers and borrowers apply for credit. Some borrowers are informed and direct their application toward the lowest offers while others are uninformed and apply randomly. Equilibrium features price dispersion - controlling for a borrower's default risk, both high- and low-cost lending exist. Importantly, the distribution of loan prices and the extent of lenders' market power are disciplined by borrowers' outside options. We calibrate the model to match characteristics of the unsecured consumer credit market, including high-cost options such as payday loans. We use the calibrated model to evaluate interest rate ceilings. In a model with a competitive financial market, ceilings can only harm borrower welfare. In contrast, with lender market power, interest rate ceilings can raise borrower welfare by reducing markups, but that requires households to have some degree of financial illiteracy (lack of information about interest rates).
Keywords: D15; D43; D60; D83; E21; G51; 330; Interest rates; Credit and credit aggregates; Financial markets